METODE PEMBELAJARAN BAHASA ARAB KOMUNIKATIF (METODE SUGGESTOPEDIADAN METODE COMMUNITY LANGUAGE LEARNING) - Hafidah _ (Jurnal Forum Tarbiyah, 2012)
Language ability is not only determined by external factors but also internal ones. Every human being owns an innate ability; that is the ability to learn innate language called LAD (language acquisition device /Â Â  ïº”ï»ï» ï»Ÿïº ïºïºŽïº´ïº˜ï»›ïº ïº¯ïºŽï»¬ïºŸ Suggestopedia method is intended to divert learnersâ€™ negative influence and suggestion, in which those are usually not realized, and to direct students to optimize positive learning. This means that the creation of an optimal learning environment is needed. Positive sentences attached to the wall; or mounted posters featuring the targetÂ  language of grammatical information are displayed with the intention to deliver benefits to the learners. The subject matters are given in two stages, namely the receptive and the activation stages. Community Language Learning Methods grew from an idea to apply the concept of psychotherapy in language teaching. This methodÂ  is based on the factor of attitude, emotion, and motivation in trying to learn a foreign language. There are five stages in this method: the embryonic, self-assortive, birth existence, reseval, and the independent stages. In this method, the teacher acts as a counselor, and learners act as clients in accordance with the fifth stage of the learning.